Indian students’ understanding of good writing influenced by their past and present experiences - De, Lopamudra (Kansas State University, 2020)
English has achieved the status of a global language and the knowledge of its usage is an absolute essential for success in any field. English is the official language in more than seventy countries, including India. Over 100 languages and about 1500 dialects are spoken in India and English is the official and academic language, along with Hindi and other vernacular languages. Due to the multilingual and multicultural setting, Indian English is constantly changing as there is a continual influence between regional dialects, thus creating a complexity within the varieties of English in the field of World Englishes (Krishnaswamy & Krishnaswamy, 2017). A wide variety of the Indian English language, as well as different levels of proficiency are seen throughout the country. Knowledge of the English language has opened new avenues for the Indian students, encouraging them to pursue higher studies in native English-speaking countries like UK and the U.S. Undergraduate Indian students in the U.S. are a population quite under-represented in research and further studies are required to understand their English learning and writing experiences as second language learners of English in the English native-speaking academic environment. This qualitative multiple case study was conducted to explore what undergraduate Indian students in the U.S. understood by good writing and in what ways have their past and present experiences influenced their understanding of good writing. This study was guided by Krashen's (1982) definition of second language acquisition and second language learning, Kachru's (1992) discussion of World Englishes through the Three Concentric Circles model and Lillis’s (2013) sociolinguistic study of English writing. This study focused on the undergraduate Indian students' past experiences of learning and acquiring English as a second language; their past experiences of learning English writing in multilingual and multicultural country like India; and their present experiences of writing in English as a second language in English native-speaking academic setting. Data was collected through interviews, and focus group discussion. Reflective memos by the researcher were used to triangulate and enhance the research experience and examine the findings. This study accepted and valued each participants' different perspectives on good writing, shaped by their past and present diverse cultural, socio-economic, and linguistic experiences. Findings revealed that the participants’ understanding of good writing was influenced by their socio-economic background, academic background, linguistic background, place of growing up, gender, self-perception, attitude towards English writing and the usage of the English language. Findings also revealed that their experiences of learning and/or acquiring English as a second language, and their experiences of writing in the intensive English program and the college composition class at the university also shaped their understanding of good writing.
Keywords: Good writing; Indian English; English as second language; Second language writing; Sociolinguistics of writing; Second language acquisition; Undergraduate Indian students